2008
DOI: 10.1002/pmic.200700977
|View full text |Cite
|
Sign up to set email alerts
|

Is the failing heart out of fuel or a worn engine running rich? A study of mitochondria in old spontaneously hypertensive rats

Abstract: Hypertension now affects about 600 million people worldwide and is a leading cause of death in the Western world. The spontaneously hypertensive rat (SHR), provides a useful model to investigate hypertensive heart failure (HF). The SHR model replicates the clinical progression of hypertension in humans, wherein early development of hypertension is followed by a long stable period of compensated cardiac hypertrophy that slowly progresses to HF. Although the hypertensive failing heart generally shows increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 56 publications
7
48
1
1
Order By: Relevance
“…A previous study found that the 3-hydroxyacylcarnitines were absent in LCAD -/-tissues and a profound deficiency of acetylcarnitine was observed in LCAD -/-hearts, indicating that the cardiomyopathy in the LCAD -/-mouse is caused primarily by a severe energy deficiency in the heart, stressing the important role of LCAD in cardiac fatty acid metabolism in the mouse (27). LCAD was elevated in SHR cardiac mitochondria (121%) (28).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study found that the 3-hydroxyacylcarnitines were absent in LCAD -/-tissues and a profound deficiency of acetylcarnitine was observed in LCAD -/-hearts, indicating that the cardiomyopathy in the LCAD -/-mouse is caused primarily by a severe energy deficiency in the heart, stressing the important role of LCAD in cardiac fatty acid metabolism in the mouse (27). LCAD was elevated in SHR cardiac mitochondria (121%) (28).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, a diminished ratio of PCr to ATP has been shown to be an excellent prognostic indicator of survival in human heart failure (112,113). Gene expression and proteomic profiling, together with ultrastructural studies, indicate that the expression of genes and proteins involved in mitochondrial energy transduction and respiration is downregulated in the late-stage failing heart (114)(115)(116)(117). In addition, several recent studies have revealed changes in the metabolome indicative of alterations (bottlenecks) in fuel oxidation and mitochondrial respiration (87,89,117).…”
Section: Energy Metabolic Derangements In the Failing Heartmentioning
confidence: 99%
“…Mitochondrial protein content was determined using a BCA protein assay (Thermo Fisher Scientifi c, San Jose, CA). High-resolution respirometry was performed using 50 µg of mitochondrial protein per 2 ml chamber with the substrate and inhibitor addition protocol previously described ( 27,31 ).…”
Section: Multidimensional Mass Spectrometry-based Shotgun Lipidomic Amentioning
confidence: 99%